Delayed Distant Intracerebral Hematoma after Ventriculoperitoneal Shunt in a Child - Gandhi, Ashok; Sundar, Vijay; Gupta, Pankaj; Sharma, Vinod; Mittal, Radhey Shyam (Journal of Pediatric Neurology, 2015)
Intracerebral hematoma following shunt surgery is a well-known but a rare complication. Usually these are encountered along the track of shunt tube. Intracerebral hematoma occurring days after shunt surgery at a location unrelated to the track of the shunt tube is very rare with only one reported case. Here, we report a case of postoperative delayed intracerebral hematoma in a pediatric age patient who presented on postoperative day 6 with such an unusual manifestation. Probable causes and management of the same are discussed.
Keywords: ventriculoperitoneal shunt; complication; child; intracerebral hematoma